Regrets after alcohol consumption following the 2008 financial crisis in Iceland: A prospective cohort study - Anna María Guðmundsdóttir 1982- (2012)
Objectives: Economic recessions have been known to affect a population´s health and well-being in numerous ways. Alcohol consumption patterns may change with economic fluctuations, however, the knowledge base on if and how the 2008 economic recession in Iceland affected alcohol intake is limited. The aim of our study was to investigate whether the economic recession in Iceland was associated with changes in alcohol consumption and regrets after drinking from 2007 (before recession) to 2009 (after onset of recession) and if socioeconomic status, financial difficulties, stress levels and social support affected potential changes. Methods: A nationally representative prospective cohort of 3,432 Icelanders answered a health related questionnaire including questions on alcohol consumption and regrets after drinking in 2007 and again in 2009. Alcohol consumption (drinking five drinks or more per one occasion) and regrets after drinking were measured by two items from The Alcohol Use Disorders Identification Test (AUDIT-Scale). Binary logistic regression was used to identify potential change in alcohol consumption and regrets after drinking in 2009, using 2007 as a reference. Results: Odds of drinking five drinks or more per one occasion remained similar between the years (overall OR=0.89; CI 0.78-1.02), the only observed subgroup difference was for the employed or otherwise active in the society. Overall regrets after drinking decreased between the years 2007 and 2009 (OR=0.85; CI 0.74-0.97). Regrets after drinking decreased for males (OR=0.82; CI 0.69-0.98), those married/cohabiting (OR=0.85; CI 0.73-0.99), for individuals with a university degree (OR=0.78; CI 0.61-0.99), the employed (OR=0.85; CI 0.73-0.98) and those active in the society (OR=0.85; CI 0.73-0.98). Those reporting high stress levels at both time points or high stress levels only in 2009 had higher risk of having regrets after drinking than those reporting low stress levels in both years (OR=2.89; CI 1.01-8.28 and OR=1.83; CI 1.07-3.12, respectively). ...